2018
DOI: 10.1002/lom3.10281
|View full text |Cite
|
Sign up to set email alerts
|

Headwater gas exchange quantified from O2 mass balances at the reach scale

Abstract: Headwater streams are important in the carbon cycle and there is a need to better parametrize and quantify exchange of carbon‐relevant gases. Thus, we characterized variability in the gas exchange coefficient (k 2) and dissolved oxygen (O2) gas transfer velocity (k) in two lowland headwaters of the River Avon (UK). The traditional one‐station open‐water method was complemented by in situ quantification of riverine sources and sinks of O2 (i.e., groundwater inflow, photosynthesis, and respiration in both the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…Given a benthic O 2 flux, it is then possible to create an oxygen budget from which gas exchange can be calculated (Rovelli et al, 2018). This method provides an indirect, but likely accurate measure of k, and enables estimating variation within a day, for example, from the effects of wind (Rovelli et al, 2018). These underwater eddy covariance methods can also directly estimate gas exchange (Berg & Pace, 2017).…”
Section: Eddy Covariance In Air or Watermentioning
confidence: 99%
See 3 more Smart Citations
“…Given a benthic O 2 flux, it is then possible to create an oxygen budget from which gas exchange can be calculated (Rovelli et al, 2018). This method provides an indirect, but likely accurate measure of k, and enables estimating variation within a day, for example, from the effects of wind (Rovelli et al, 2018). These underwater eddy covariance methods can also directly estimate gas exchange (Berg & Pace, 2017).…”
Section: Eddy Covariance In Air or Watermentioning
confidence: 99%
“…Although predicting gas exchange for any one site using models is highly uncertain, the good news is that methods for estimating gas exchange within a site are becoming easier to conduct. New empirical methods with tracer gas additions (Hall & Madinger, 2018) underwater eddy covariance (Berg & Pace, 2017;Rovelli et al, 2018), and linkages to hydrodynamics (Lorke et al, 2019) will improve estimates at any one site. Modeling oxygen dynamics allows estimating k 600 for many streams with long time series of oxygen collected for water quality purposes.…”
Section: Estimates For a Particular Streammentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed modeled K using nighttime linear regression of dissolved oxygen (Hall & Hotchkiss, 2017, supporting information Figures S5 and S6). We found that the relationship between K-ER is lowest and potential for equifinality reduced when constraining K according to a K~Q relationship, compared to using air-water gas exchange scaled to a temperature of 20°C , as in Rovelli et al (2018); supporting information Figures S7 and S8). Additionally, we removed 30 days with K values below the 1% (<3.38 d −1 ) and above the 99% (>27.21 d −1 ) quantiles to further decrease the chances of using biased metabolism estimates in our P-Q analyses (Figure S6).…”
Section: Metabolism Estimatesmentioning
confidence: 93%